Molecular diversity of Hungarian melon varieties revealed by RAPD markers - Bába, E.; Zarka, V.; Deák, T.; Pedryc, A.; Velich, I.; Bisztray, Gy. D. (International Journal of Horticultural Science, 2002)
RAPD markers were used to reveal genetic diversity between nine varieties of Cucumis melo L. and to identify the studied varieties. Of the 60 primers tested 12 primers produced polymorph patterns. A set of 4 primers was sufficient for distinction the nine investigated melon varieties.